2006
DOI: 10.1161/01.res.0000201960.04223.3c
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinases in Cardiovascular Physiology and Pathophysiology

Abstract: Abstract-Rho kinases (ROCKs) are the first and the best-characterized effectors of the small G-protein RhoA. In addition to their effect on actin organization, or through this effect, ROCKs have been found to regulate a wide range of fundamental cell functions such as contraction, motility, proliferation, and apoptosis. Abnormal activation of the RhoA/ROCK pathway has been observed in major cardiovascular disorders such as atherosclerosis, restenosis, hypertension, pulmonary hypertension, and cardiac hypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
417
2
6

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(438 citation statements)
references
References 149 publications
13
417
2
6
Order By: Relevance
“…The consensus sequence of ROCK substrates is R/K-X-S/T or R/K-X-X-S/T (R, arginine; K, lysine; S, serine; T, threonine) [4,37,41,61,83]. More than 20 ROCK substrates have been identified (reviewed in refs [51,78,113]). …”
Section: Substrates Of Rockmentioning
confidence: 99%
See 1 more Smart Citation
“…The consensus sequence of ROCK substrates is R/K-X-S/T or R/K-X-X-S/T (R, arginine; K, lysine; S, serine; T, threonine) [4,37,41,61,83]. More than 20 ROCK substrates have been identified (reviewed in refs [51,78,113]). …”
Section: Substrates Of Rockmentioning
confidence: 99%
“…During the last decade, the Rho/ROCK signaling pathway has attracted much attention in various research fields, and more than 2,000 articles have been published; many of which focus on ROCK function in the cardiovascular system, central nervous system, cancers and embryonic development. Several excellent recent reviews have covered large aspects [11,33,51,78,94,97,113,123]. The up to date progress in the translational research has demonstrated that ROCK is an important therapeutic target for the treatment of various cardiovascular diseases and neurological disorders, cancers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…RhoA, a small GTPase, is a member of the Ras superfamily and has roles in cell adhesion, migration, cytoskeletal organization as well as a variety of other cellular functions (139). TG2 can activate RhoA by two mechanisms.…”
Section: Transglutaminases and Signal Transductionmentioning
confidence: 99%
“…A major substrate of Rho kinase is myosin phosphatase target subunit (MYPT-1), and phosphorylation of MYPT-1 by Rho kinase leads to inhibition of myosin phosphatase activity, resulting in increased myosin L chain phosphorylation and actin-myosin-mediated contractility (18). Rho kinase activation can also be induced through Rho-independent mechanisms.…”
mentioning
confidence: 99%
“…Rho kinase activation can also be induced through Rho-independent mechanisms. Binding of lipid messengers, including arachidonic acid or sphingosine phosphorylcholine, to Rho kinase or proteolytic cleavage of Rho kinase by caspase 3 or granzyme B can efficiently activate Rho kinase independent of Rho (18).…”
mentioning
confidence: 99%